2021
DOI: 10.1016/j.resuscitation.2021.07.012
|View full text |Cite
|
Sign up to set email alerts
|

A multi-centre randomised controlled trial of respiratory function monitoring during stabilisation of very preterm infants at birth

Abstract: Aim: To determine whether the use of a respiratory function monitor (RFM) during PPV of extremely preterm infants at birth, compared with no RFM, leads to an increase in percentage of inflations with an expiratory tidal volume (Vte) within a predefined target range. Methods: Unmasked, randomised clinical trial conducted October 2013 -May 2019 in 7 neonatal intensive care units in 6 countries. Very preterm infants (24-27 weeks of gestation) receiving PPV at birth were randomised to have a RFM screen visible or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
60
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(63 citation statements)
references
References 38 publications
3
60
0
Order By: Relevance
“…In comparison, Zeballos et al reported significantly lower V Te in the RFM visible versus no RFM group with 5.8 (4.7–6.8) and 7 (5.7–9.2) mL/kg (p<0.001), respectively 34. Van Zanten et al reported a non-significant difference in median (IQR) V Te between the RFM group and no RFM group (5.1 (4–7.1) and 5.9 (4.2–8.4) mL/kg, p=0.057) 35…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In comparison, Zeballos et al reported significantly lower V Te in the RFM visible versus no RFM group with 5.8 (4.7–6.8) and 7 (5.7–9.2) mL/kg (p<0.001), respectively 34. Van Zanten et al reported a non-significant difference in median (IQR) V Te between the RFM group and no RFM group (5.1 (4–7.1) and 5.9 (4.2–8.4) mL/kg, p=0.057) 35…”
Section: Resultsmentioning
confidence: 99%
“…The full text of 36 studies was assessed for eligibility. After review, three RCTs were included in the analysis 33–35. The PRISMA flow diagram is presented in figure 1, study characteristics in table 1 and the GRADE Assessment of Evidence table for key prespecified outcomes shown in table 2.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The neonatologists evaluated this trial individually, as they were asked about their general understanding and experience with this study and obstacles and possible improvements with regard to the PB-CPAP protocol specifically. Physiological outcomes included SpO 2 , FiO 2 , SpO 2 /FiO 2 ratio, heart rate, duration of hypoxia [SpO 2 <25th percentile of Dawson's target ranges (27)] and bradycardia (heart rate <100 bpm) during the first 5 and 10 min after birth. Respiratory effort parameters included breathing rate, inter-breath interval variability, minute volume, inspired tidal volume, peak inspiratory flow rate (PIFR) and the use of iPPV and caffeine.…”
Section: Methodsmentioning
confidence: 99%
“…The sample size calculation is based on infants who were born in the LUMC, participated in DR studies ( 11 , 28 ) and received 5–8 cmH 2 O CPAP. Infants ( n = 78) achieved a mean SpO 2 of 59% ± 13 in the first 5 min after birth.…”
Section: Methodsmentioning
confidence: 99%